Nanosized Zincated Hydroxyapatite as a Promising Heterogeneous Photo-Fenton-Like Catalyst for Methylene Blue Degradation - Van Dat Doan; Van Thuan Le; Thi Thanh Nhi Le; Hoai Thuong Nguyen (Advances in Materials Science and Engineering)
This study is devoted to synthesis of nanosized zincated hydroxyapatite (Zn-HA) and its utilization as a heterogeneous photo-Fenton-like catalyst for degradation of methylene blue (MB) in aqueous solution. The prepared catalyst was characterized by various techniques such as X-ray diffraction, scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray, and Fourier transform infrared spectroscopy. The catalytic activity of Zn-HA towards MB and the effects of various experimental factors such as pH, zinc substitution degrees, initial MB concentration, and H2O2 dosage were studied in detail. The results showed that the zinc substitution degree of 0.4 is optimal to get the highest degradation efficiency under conditions of pH = 10, H2O2 dosage of 0.05 M, and MB concentration of 30 mg/L for a contact time of 120 min. The degradation mechanism was proposed and discussed thoroughly. Besides, the ability of long-term use for the synthesized catalyst was also evaluated.